Gilles Deleuze and Education - Baranova, Jūratė (European Journal of Social Science Education and Research, 2018)
This article raises the question of the possibility to use some theoretical insights of Deleuze and Guattari for solving particular problems arising in education. The author discusses the concept of bodymind education formulated by Semetsky from the Deleze’s example of learning as swimming. The author doubts if learning as representation is not valuable in some unexpected situations. She also describes the real example of the successful bodymind learner who experienced failure in university studies in order to involve the Deleuzian/Guattarian opposition to vertical learning and the idea of transversality as the possible solution for unsuccessful learning in university situation.
Keywords: Deleuze, Guattari, bodymind learning, vertical education, transversality, schizoanalysis